Новые находки ископаемых полевок рода Pliomys (Rodentia, Microtidae) - Несин, В.А. (Вестник зоологии, 1983)
Two fossil representatives of the genus Pliomys Mehely are described as new: P. uerainicus topacevskii ssp. n. differs from nomenotypic subspecies by lower tracks on the lateral teeth surface and by frequency of M, complicated paraconide; P. jalpugensis sp. n. differs from allied species by double dentine islet M;. With respect to track development degree on M, and paraconide it occupies an intermediate position between P. kowalskii Schevtschenko and P. hungaricus Kormos.